Sorte moral e responsabilidade - Silva, Paulo Henrique de Toledo da (2015)
In the present work, we seek to elucidate the relations between the problem of moral luck and our assignments of responsibility. The problem of moral luck emerges from two dimensions of human life. On the one side, we are autonomous and rational beings, we have control over our actions and are moral agents. On the other side, we are vulnerable to every sort of external contingency that eliminates the complete control we have over our actions and their results. The contingency, also, has a significant weight on the formation of our character and personality. Therefore, the problem of moral luck takes a real importance: how can we assign responsibility to the agents, given that a lot of what configures a moral action are contingent elements? The research was elaborated based on Bernard Williams and Thomas Nagel s articles on Moral luck. Williams, in his article, seeks to show that morality, as we conceive it, is (in fact) distant from our moral evaluations. Williams introduces the role of regret and recognizes the need to understand moral justification as retrospective. Nagel, in turn, finds the center of the moral luck problem in the control principle. In trying to understand how we assign responsibility to an agent for things beyond his control, Nagel defines four methods in which luck influences our moral judgements, and lists the kinds of moral luck: resultant, circumstantial, constitutive and causal luck. Finally, we take a look at critiques pertinent to the moral luck and responsibility problem, both negating and accepting the influence of luck in moral responsibility. From the epistemic argument and Zimmerman s postulates to Walker s pure agency critique and Otsuka s strawsonian considerations about reactive attitudes.